Advertisement
Guest User

Untitled

a guest
Aug 23rd, 2017
81
0
Never
Not a member of Pastebin yet? Sign Up, it unlocks many cool features!
C 1.06 KB | None | 0 0
  1. #include <stdio.h>
  2. #include <stdlib.h>
  3.  
  4. int main(int argc, char* argv[]) {
  5.    int x = 3;
  6.    int y = 2;
  7.    int z = 5;
  8.    int w = 3;
  9.    int a = 2;
  10.    int b = 11;
  11.    int c = 4;
  12.    int d = 7;
  13.    int e = 4;
  14.    x *= (x*y*y - 1) * (y*x*x - 1);
  15.    y *= y*y*x*( 10*(y + 1) * (y + 1) * y - 1);
  16.    x *= w*y + z*(22*z + w)*(8*z*z - w);
  17.    y *= w*w*w*z*z;
  18.    z = x - ((1 << (w + z)) + w + z - 1)*((1 << a*(w + z)) + a*z*z*z*(z + w - 1) + w);
  19.    w = x + w*a*(a + w)*(a*w + 1)*((1 << (a*a*a)) - 10*a - 4*w - 1)*((a*a*a + a)*100 + w*w);
  20.    a *= a*a*a*a*a*a*a*a*a*(b/2)*(b + a)*(3*b - a)*(a*b*b + a*a*b - a - a/2);
  21.    a += y;
  22.    b = y + c*(c/2)*(c + 1)*(b*b*b + c*((2*c-1)*b + c + c/2));
  23.    c = a + (c - 1)*(c - 1)*((c-1)*c - 1)*(c*c*(c-1)*(c+1) + 10*c + (c - 1))*(1000*c - 100*c + 10*c + 2*c*c + c + 1) - (c - 1);
  24.    d = b + (e - 1)*(e - 1)*(d + e + e/2)*((e*d/2) + (e + 1))*(100*e + 10*e + e + 2*d + d/2)*(200*e - 20*e + e + d*d - d/2 - 1);
  25.    e = (e - e/e)*((e - e/e)*e + e/e)*(((e/e) + (e/e))*e*e*e*e + e*e + e*e + e - e/e);
  26.    printf("%s\n", &x);
  27.    return EXIT_SUCCESS;
  28. }
Advertisement
Add Comment
Please, Sign In to add comment
Advertisement